Surgical aspects of Hashimoto's disease - Müller Gras, Augusto J; Font, Francisco; Cordero, Miguel; Ribero, Gustavo; Delgado, Bolívar (Cirugía del Uruguay, 1992)
As regards a retrospective series of 55 patients, 34 of whom were operated on, the author analyses the diagnostica/ value of thyroid cytology and antithyroid antibodies dosage for Hashimoto 's disease. In the group of operated patients. low sensitivity of cytology stands out.